Pengembangan Multimedia IPA Berbasis Flash untuk Meningkatkan Literasi Sains Siswa SMP - Adhiesta Kurnia Fikri Rosandi; Tjandrakirana Tjandrakirana; Imam Supardi (IKIP Mataram, 2016)
This research aims to develop Flash-based IPA multimedia that is valid, practical, and effective to train students' scientific literacy on the subject of Excretion Systems in humans. The target of the study was multimedia science that was tested on 35 grade VIII junior high school students with the design of One-Group Pretest-Posttest Design. Quantitative-qualitative data analysis with results: (a) valid multimedia validation (3.5); (b) the implementation of learning is very good (3.7); (c) student activities reach 97.9%; positive student response (97%); (d) students' scientific literacy abilities increase from level 1b (students demonstrate little facts in content, procedural and epistemic knowledge, evaluate and design questions and interpret data in a few situations) to level 3 (students can use content, procedural, and epistemic knowledge to explain, evaluate and design scientific questions and interpret data in several life situations) to level 6 (students can use content, procedural knowledge, and design questions and interpret data in complex situations to reach the highest level in the cognitive domain). The conclusion of this study, that Flash-based science multimedia is feasible to train science literacy of junior high school students.